2015
DOI: 10.1186/s13071-015-0763-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of tick-borne rickettsial and protozoan pathogens in domestic dogs from Turkey

Abstract: BackgroundCanine tick-borne parasites have emerged in recent years, showing a wider geographic distribution and increased global prevalence. In addition to their veterinary importance, domestic dogs play an important role in the transmission cycles of some agents by acting as reservoirs and sentinels. This study investigated Babesia, Theileria, Anaplasma, and Ehrlichia species in asymptomatic dogs in ten provinces of Turkey.MethodsDNA obtained from blood samples collected from 757 domestic dogs (243 stray, 351… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
59
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 37 publications
4
59
6
Order By: Relevance
“…An analysis of risk factors indicated that male dogs were more often infected with E. canis than the females, but this association was statistically non-significant (P = 0.15) confirming previous studies reporting that there is no correlation between the sex and the presence of E. canis infection in dogs (Rani et al 2011;Aktas et al 2015). Similarly, data regarding the age of the animals indicated that animals less than 1-year-old were more prone to E. canis infection compared with animals older than 1 year old, but this association was also statistically non-significant (P > 0.05) indicating that neither sex nor the specific stage of life made subjects more prone to E. canis infection.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…An analysis of risk factors indicated that male dogs were more often infected with E. canis than the females, but this association was statistically non-significant (P = 0.15) confirming previous studies reporting that there is no correlation between the sex and the presence of E. canis infection in dogs (Rani et al 2011;Aktas et al 2015). Similarly, data regarding the age of the animals indicated that animals less than 1-year-old were more prone to E. canis infection compared with animals older than 1 year old, but this association was also statistically non-significant (P > 0.05) indicating that neither sex nor the specific stage of life made subjects more prone to E. canis infection.…”
Section: Discussionsupporting
confidence: 61%
“…canis has been detected and reported in dogs from many parts of the world Rani et al 2011;Sasaki et al 2012;Ybañez et al 2012;Nazari et al 2013;Aktas et al 2015;Inpankaew et al 2016). An analysis of our results revealed a 28% overall prevalence of E. canis (N = 42) in the studied blood samples from the three districts, suggesting that E. canis is prevalent in Punjab province (Table 1) but the prevalence of E. canis varied significantly between three sampling areas indicating that geographical features and climatic conditions do affect the parasite prevalence (Rani et al 2011;Mircean et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Published studies of babesiosis in Turkey have identified B. canis [11][12][13][14][15][16] , B. vogeli [13,15,[17][18][19] , B. gibsoni [20] , and an unnamed Babesia spp. [15] in dogs.…”
Section: Introductionmentioning
confidence: 99%